Penerapan Fungsi Manajemen dalam Pengelolaan Kostum di Sanggar Tari - Grace Evelyn Hidayat; Tsania Azizah Zadal Faroh; Berliana Purwanto Shakhib; Sri Endah Wahyuningsih (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Costume management is a crucial aspect of ensuring the quality of dance performances, as it plays a vital role in establishing character, aesthetics, and cultural identity. This study aims to analyze the application of management functions in costume management within a dance studio. A qualitative approach utilizing a case study method was employed. Data were collected through in-depth interviews, observation, and documentation, and subsequently analyzed using the interactive analysis model developed by Miles, Huberman, and Saldaña, which encompasses data reduction, data display, and conclusion drawing. Data validity was verified through source and technique triangulation. The results indicate that management functions—specifically planning, organizing, implementing, and supervising—have been applied to costume management. Planning involves costume procurement and usage scheduling; organizing entails task allocation and the provision of supporting facilities; implementation involves the use of operational resources and coordination among members; and supervision involves monitoring costume usage and condition. However, the application of these functions is not yet optimal due to resource limitations, unsystematic inventory record-keeping, and a lack of structured documentation for supervision mechanisms. The findings suggest that while facility availability and resource support contribute to the smooth operation of costume management, achieving true effectiveness requires a more organized management system. Therefore, strengthening administration, standardizing procedures, and enhancing supervision systems are essential to ensure the sustainability of costume management in the dance studio.